The Interconnection between Energy Efficiency and CO2 Mitigation in the Development of Multifamily Buildings - Rodríguez, J. S. Támara-; Vallejos, C. M. Chavarry-; Reyes, L. J. Chavarría-; Cabana, L. T. Javier-; Ramírez, A. E. Gómez-; Roque, R. M. Reyes-; Vergara, E. A. Milla- (International Journal of Membrane Science and Technology, 2023)
This paper aims to analyze energy efficiency in the life cycle of multifamily buildings in Metropolitan Lima, Peru, to improve productivity, competitiveness and reduce environmental impact. Decarbonization technology has been investigated, which focuses on reducing or eliminating carbon dioxide (CO2) emissions from energy sources used by buildings, thus contributing to the fight against climate change. This study collected statistical information from real estate projects to identify the primary means of energy consumption and greenhouse gas emissions, such as carbon dioxide (CO2). The objective was to maintain an effective balance between costs, time, and quality, thus ensuring the productivity and profitability of the buildings. The research method was deductive, using a quantitative approach to analyze numerical data on energy efficiency in multifamily buildings. The applied orientation allowed linking the findings with the concrete improvement of construction and operational practices. The study is framed within a descriptive and correlational approach, allowing the identification of relationships between energy efficiency and CO2 emissions and explaining the relationship between these variables. The study design was non-experimental, as no controlled manipulations of variables were performed. A cross-cutting and forward-looking approach was adopted, analyzing the data at a single point and considering possible future effects of the energy efficiency measures implemented. As a result of the analysis, it was found that the application of energy efficiency measures allowed a 25.00% reduction in CO2 emissions. This finding highlights the relevance of energy efficiency as an effective tool to mitigate the environmental impact of multifamily buildings in the region. In conclusion, this study has shown that implementing energy efficiency practices can significantly reduce CO2 emissions in multifamily buildings in Metropolitan Lima. These results provide a solid basis for adopting sustainable measures in the development and operation of facilities, aiming towards more environmentally friendly construction and contributing to the fight against climate change.